2015
DOI: 10.1007/s12160-015-9726-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Stress Management for Healthy Women at Risk for Breast Cancer: a Novel Application of a Proven Intervention

Abstract: Background Women at risk for breast cancer report elevated psychological distress, which has been adversely associated with cancer-relevant behaviors and biology. Purpose The present study sought to examine the effects of a 10-week cognitive behavioral stress management (CBSM) group intervention on distress among women with a family history of breast cancer. Methods Participants were randomly assigned to CBSM (N= 82) or a wait-list comparison group (N=76). Baseline to post-intervention effects of CBSM on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
1
9
1
1
Order By: Relevance
“…Notably, participants who used the website’s relaxation and meditation recording feature more often during the intervention reported a decrease in perceived stress after the intervention. This is consistent with findings of similar interventions with human immunodeficiency virus (HIV)-positive men [ 49 ], men with prostate cancer [ 25 ], women at risk for breast cancer [ 50 ], and women with breast cancer [ 48 , 51 ]. Each of these studies reported that the frequency of at-home practice or improvements in perceived ability to relax was associated with psychological and physiological benefits.…”
Section: Discussionsupporting
confidence: 84%
“…Notably, participants who used the website’s relaxation and meditation recording feature more often during the intervention reported a decrease in perceived stress after the intervention. This is consistent with findings of similar interventions with human immunodeficiency virus (HIV)-positive men [ 49 ], men with prostate cancer [ 25 ], women at risk for breast cancer [ 50 ], and women with breast cancer [ 48 , 51 ]. Each of these studies reported that the frequency of at-home practice or improvements in perceived ability to relax was associated with psychological and physiological benefits.…”
Section: Discussionsupporting
confidence: 84%
“…Reductions in cortisol levels or normalization of diurnal cortisol patterns have also been reported 150,152 . The changes in immunological and endocrine responses associated with psychological interventions do not seem only to exert a beneficial impact on coping strategies, stress relieving, affective symptoms and on quality of life measures [153][154][155] , but there is also some evidence of a long-lasting effect on survival. For instance, in a study with a 11-year follow-up of breast cancer patients, psychological treatment was effective in reducing the risk of recurrence (hazard ratio [HR]= 0.55; 95% CI 0.28-0.93) and death from breast cancer (HR = 0.44; 95% CI 0.32-0.957) 156 .…”
Section: Effects Of Psychological Treatments On Depression In Patientmentioning
confidence: 99%
“…In prior work, higher levels of depressive symptoms were related to greater ICV in women undergoing surgery for cancer [31]. It will be worthwhile in future investigations to examine whether changes in distress are also related to reductions in ICV between groups as the intervention described herein mitigated depressive symptoms and perceived stress [25]. Third, only 4 time points of salivary collection were used to generate the ICV estimate and a larger, more robust sampling protocol may yield different results.…”
Section: Discussionmentioning
confidence: 95%
“…Women were randomized to a cognitive behavioral stress management (CBSM) intervention or to a wait-list control condition. This 10-week intervention was shown to reduce perceived stress and depressive symptoms and, further, those that practiced relaxation more frequently demonstrated the greatest reductions in these parameters [25]. For the current secondary analysis, it was hypothesized that women randomized to the CBSM condition would demonstrate lower ICV immediately after the intervention and during the immediate follow-up period (1 month post-intervention).…”
Section: Introductionmentioning
confidence: 99%